RATIONAL CYTOPROTECTIVE THERAPY OF ISCHEMIC HEART DISEASE CONCOMITANT WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Potyazhenko, M.; Katerenchuk, P.; Nastroha, T.V.; Nastroha, V.S. (World of Medicine and Biology, 2015)
The article presents the experience of treatment of patients with coronary artery disease comorbidity and COPD with the use in the treatment of cardio – and endothelium-protective drug – kardyoarhynyna. Positive clinical dynamics in patients receiving combined therapy with application solution kardyoarhynyna contributed to improving the quality of life, increase tolerance to physical activity, shortening patient stays in hospital by 1.6 days.